Orthodontic Treatment Of Osseous Reverse Jaw During Mixed Dentition Period - Jing, Zhang (International dental journal, 2025)
Used Facemask protraction therapy and MRC Trainer a 9-year-old male . Anterior crossbite involving teeth: #53, #12, #11, #21, #22, #63. Bilateral molar mesial relationship. Low tongue posture with associated tongue thrust swallowing habit. Cephalometric analysis confirmed a Class III skeletal pattern with a normally positioned maxilla and mandibular prognathism. Phase I: Utilization of a Hyrax-type maxillary expansion appliance with occlusal coverage combined with maxillary facemask protraction therapy to correct anterior crossbite. Phase II: Application of an MRC Trainer®to correct low tongue posture and tongue thrust swallowing habit, thereby maintaining occlusal stability. The final occlusion achieved shallow anterior overbite and overjet with clinically satisfactory improvement in facial profile. The etiology of Class III malocclusion is complex and multifactorial. This paradigm shift recognizes that the dynamics of orofacial musculature directly impact dentofacial development and critically influence post-treatment stability following orthodontic intervention. The management of skeletal anterior crossbite during the mixed dentition period requires meticulous consideration of musculature's profound impact on dentition, arch configuration, and craniofacial morphology in both diagnostic evaluation and treatment planning. Achieving satisfactory therapeutic outcomes necessitates the implementation of integrated neuromuscular modulation strategies combined with orthopedic interventions to address the multifaceted nature of this malocclusion.